EARLY UKRAINIAN SONNET: FROM MAINTENANCE TO FORM - Lisenco, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the separate aspects of evolution of the early Ukrainian sonnet, and also his form creation ХІХ beginning of ХХ centuries are reflected on a border with the sonnets of neoclassicisms. It is led to, that to the Ukrainian sonnet inherent uneven development. From borrowing by the poets of beginning of ХІХ age of only formal signs a sonnet attained tops in the Ukrainian poetry due to creation of Ivan Franco, Uliana Cravchenko, and also Lesia Ukrainka, and at the end of ХІХ - to beginning of ХХ age happened the decline of this lyric genre, by the revival of which we thank to the pleads of Ukrainian neoclassicisms, personal Nick Zerov, took place.